Wormhole approach to control in distributed computing has direct relation to physics - Lori, Nicolas Francisco (2017)
The topic of Wormholes in distributed computing is about creating two different realms with different characteristics, the synchronous Wormholes and the asynchronous payload with the goal of using the wormholes to control the synchronism of the payload processes. We describe the characteristics of Wormholes in distributed computing, and relate them to issues in Physics, specifically, wormholes in general relativity and entanglement in quantum mechanics. The entanglement in quantum mechanics is about the existence of fixed relations between different physical systems as if they were still the same system. The entanglement is made evident by the occurrence of decoherence, which transform the multiple outcome possibilities of quantum systems into a single outcome “classical physics”-like objective reality. It is here presented the similarity between the decoherence process in quantum physics and the consensus problem in distributed computing. The approach to quantum mechanics used is quantum Darwinism, a Darwinian approach to decoherence where the environment controls the outcome of a measurement. It is here proposed that wormhole systems can be used to implement environment-based control of distributed computing systems.